2022
DOI: 10.3390/particles5030024
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of Dark Matter Admixed Neutron Star Binaries

Abstract: Multi-messenger observations of compact binary mergers provide a new way to constrain the nature of dark matter that may accumulate in and around neutron stars. In this article, we extend the infrastructure of our numerical-relativity code BAM to enable the simulation of neutron stars that contain an additional mirror dark matter component. We perform single star tests to verify our code and the first binary neutron star simulations of this kind. We find that the presence of dark matter reduces the lifetime of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 79 publications
1
9
1
Order By: Relevance
“…We have shown that the presence of DM can delay the point of mass-shedding to a later stage of the inspiral, i. e., towards closer separations. This is in accordance with the findings in numerical evolutions of two-fluid binary mergers [25]. In the case of a DM halo, mass shedding could occur much earlier than for the baryonic component.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We have shown that the presence of DM can delay the point of mass-shedding to a later stage of the inspiral, i. e., towards closer separations. This is in accordance with the findings in numerical evolutions of two-fluid binary mergers [25]. In the case of a DM halo, mass shedding could occur much earlier than for the baryonic component.…”
Section: Discussionsupporting
confidence: 92%
“…These quasiequlibrium configurations can be used as initial data for NR inspiral simulations of DM admixed NS binaries. The BAM code can already evolve mirror DM [25] and could be easily extended to allow for general EoS for the DM fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results summarized above differ from other recent studies on mirror matter admixture on NSs [8,49,50] and binary NS mergers [51]. These other studies explored mirror matter candidates that, apart from discrete symmetries, are identical to SM particles.…”
Section: Introductioncontrasting
confidence: 81%
“…In addition to LIGO/Virgo/KAGRA results Abbott et al (2021), this bound could be further constrain thanks to the upcoming GW missions such as LISA Baker et al (2019) and Einstein telescopes Maggiore et al (2020). Note that the presence of DM core/halo should be precisely taken into account in numerical-relativity simulations to compute GW spectrum and waveforms during merger and postmerger phases of a binary system containing at least a DM admixed NS Ellis et al (2018a); Giudice et al (2016); Bezares et al (2019); Emma et al (2022).…”
Section: Conclusion and Remarksmentioning
confidence: 97%